Factors that play a role in the implementation of the boys 2 men (B2M) programme : case study from the Limpopo Province - Mamabolo, Mmapheto Robert (My University, 2013)
In 2010, the Development Facilitation and Training Institute (DevFTI) (University of Limpopo) embarked on the process of expanding the Sex and Relationships Education Programme, Boys 2 Men as part of its projects. During the process, it became apparent that there was a need to evaluate the implementation process of the B2M programme by CBOs in the selected district municipalities in the Limpopo Province. The B2M project is a programme that was first put into place in 2000 as one of the ways of addressing issues of sex and relationships education for young men in especially rural areas that have limited access to such programmes. To evaluate this programme, this current study intended to explore enabling and/or hindering factors as well as experiences of trained facilitators in the implementation of the B2M programme. A qualitative case study research design was conducted using semi-structured face-to-face group interviews. As the targeted population was small a census was used (i.e. total sample =24). Content analysis method was used, looking at themes given by respondents to highlight the facilitating and/or hindering factors as well as experiences of the trained facilitators during the implementation of the B2M programme. The results indicated that, amongst others, the significant enabling factors for implementation included support by the community, host CBO and university partners; availability of facilitation material as well as infrastructural and financial support. Whilst, the significant hindering factors included lack of finance; lack of interest from the host CBOs, limited resources; and unclear terms of reference. Based on the results, it was therefore recommended that the programme set clear and specific terms of reference; facilitators be given tokens of appreciation; clear monitoring and evaluation tools be put into place; sufficient support be provided by university partners continuously; funding that is specific for the implementation of this programme be sought so as not to drain CBO financial and manpower resources; and work with facilitators and CBOs that have interest in issues that are almost similar to those that are addressed by the B2M programme. From the research results it could be concluded that this programme is valuable and it is therefore important to consider continuing with it provided that the above recommendations are considered in future implementation
Thesis ( M.Dev.) -- University of Limpopo, 2013
Keywords: Sex relationship education; Young men; Sex instruction for boys; AIDS (Disease) -- South Africa